Biometric and biochemical characteristics of glass eels (Anguilla spp.) collected from Cimandiri Estuary, Sukabumi Regency, Indonesia - Kamal, Mohammad Mukhlis; Wildan, Dudi Muhammad; Tatag Budiardi; Agus Oman Sudrajat; Ronny Irawan Wahju; Ridwan Affandi; Mala Nurilmala (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Glass eel viability determines the success of cultivation and governs the recruitment variability, as seeds in aquaculture and its wild population, respectively. This study aims to examine the quality of glass eel using biometric measurements coupled proximate contents. Glass eel collection was made montly by using lift-net like fishing gear in Cimandiry Estuary during December 2020 - April 2021. Biometric aspects were examined on length, weight, eye diameter, heart, and liver, whereas proximate was run on proteins, fats, carbohydrates, and ash. The results showed that length and weight steadily increased between month, though the condition factor was indifferent. Eye diameter and mouth opening confirm the vision of diurnal predatory fish. Heart and liver have demonstrated the metabolism capability and fast swimming fish favors to migratory catadromous fish. Proteins, fats, carbohydrates, and ash fluctuated between month, though insignificant between month comparison. No clear confirmation of proximate analysis on biometric characters. However, the glass eels with largest size in April might be best for aquaculture.